Land exchange as a constituent of the existing agricultural land tenures and land ownerships improvement in Ukraine - Malashevska О. (Land Management, Cadastre and Land Monitoring, 2019)
The issue of the existing agricultural land improvement effectiveness in the course of land reform is scrutinized in the article. The research relevance is predefined by the need for the fragmented land optimization as a constituent of the sustainable land tenure in Ukraine. Land exchange substantiation in the course of the existing agricultural land tenure and land ownership improvement under current social and economic conditions is the goal of the research. Key aspects of land exchange aiming at land tenure optimization within the agricultural land mass in accordance to the legislation in effect have been exemplified. Sources of the existing agricultural land tenures and land ownerships drawbacks have been singled out. Land tenure areas of agricultural enterprises situated in Ukraine and Kyiv Region have been analyzed. Land exchange based on a set of the qualitative, spatial and technological characteristics has been suggested. Land exchange has been realized based on the example of one of agricultural enterprises in Kyiv Region. As the result, the improvement of the agricultural enterprise land tenure spatial characteristics as a factor of agricultural activity effectiveness has been achieved. The research results can be used at the existing land tenure and land ownership improvement in accordance to the legislation, the land consolidation strategy development in Ukraine, land owners and land users private efforts and the scientific researches in the future. Key words: land exchange, land sublease, agricultural land, agricultural activity effectiveness, land reform.